Atom‐Economic Catalytic Direct Substitution of N, O‐Acetals with Simple Ketones. Issue 30 (15th August 2017) - Touati, Bahria; El Bouakher, Abderrahman; Azizi, Mohamed Salah; Taillier, Catherine; Ben Othman, Raja; Trabelsi‐Ayadi, Malika; Antoniotti, Sylvain; Duñach, Elisabet; Dalla, Vincent
Abstract : A general and powerful catalytic protocol for the direct amidoalkylation of simple enolizable ketones is described, with use of the Lewis superacid Sn(NTf2 )4 as a catalyst under thermal conditions. A complete and rational study directed towards the development of efficient conditions for the coupling of a wide range of reaction partner combinations, including the most recalcitrant ones, is presented. The synthetic potential of the reaction is demonstrated through the use of a large set of both carbonyl and N, O‐acetalic substrates, providing the corresponding amidoalkylated ketones in 49–99 % yield, by using very low catalyst loadings (≤ 1 mol‐%). Abstract : A powerful catalytic protocol for the direct amidoalkylation of simple enolizable ketones with use of Lewis superacid Sn(NTf2 )4 as a catalyst is described. Couplings of a large set of both carbonyl and N, O‐acetalic substrates (mostly the simplest OH‐hemiaminals) proceed with very low catalyst loadings (≤ 1 mol‐%) and provide the corresponding amidoalkylated ketones in high yields (up to 99 %).